(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Mires are known as consistent environmental archives, but humic acids are the fraction of peat that is most recalcitrant and refractory to organic matter degradation, thus data on environmental changes during mire development can be recorded into them. This work was focused on the studies of stable isotopic ratios delta carbon-13 and delta nitrogen-15, and their distribution in humic acids within fen peat layers of different depths and peat composition. The variations in delta carbon-13 reflect isotopic variations in peat-forming plants over time and can be considered as a function of photosynthetic pathway that is being used to fix carbon dioxide. At the same time, variations in delta nitrogen-15 show nitrogen fixation in peat-forming plants and can be traced along with peat decomposition degree and depth. Properties of humic acids were studied in 2018 at 3 fens located in Latvia and Southern Finland, and comparatively they show properties. The method used for the determination of stable isotopes was the isotope-ratio mass spectrometry that was performed in the Faculty of Chemistry, University of Latvia. Results on delta carbon-13 indicate signal of C3 peat-forming plants, while signal of C4 peat-forming plants is not evident, which can be explained by non-efficient carbon dioxide fixation in fen vegetation. Results on delta nitrogen-15 show variations in nitrogen fixation in fen vegetation. Data show nitrogen fixation in terrestrial plants, however significant shifts in absolute isotope values indicate dependence on variations in peat decomposition degree and botanical composition. Data suggest that differences in peat botanical composition, decomposition degree and site dependent characteristics reflect in differences in delta carbon-13 and delta nitrogen-15 variations